2014
DOI: 10.4067/s0718-16202014000100006
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and Antioxidant Performance Are Differentially Affected by Short-Term Nitrogen Supply in Highbush Blueberry Cultivars at the Short-Term

Abstract: E. Yañez-Mansilla, P. Cartes, M. Reyes-Díaz, A. Ribera-Fonseca, and M. Alberdi. 2014. Photosynthetic and antioxidant performance are differentially affected by short-term nitrogen supply in highbush blueberry cultivars. Cien. Inv. Agr. 41(1): 61-70. Nitrogen (N) is an essential nutrient for photosynthesis and may influence phenolic compound synthesis in higher plants. The effect of different amounts of N (0 to 38 mM) provided on a short-term (4 d) basis on the photosynthetic and antioxidant performance of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
2
11
1
Order By: Relevance
“…The elimination of H 2 O 2 might be due to the immediate strengthening of SOD, CAT, and POD activities (Figure 8), and the increased content of free amino acids (Figure 5E,F) by higher nitrogen application. Moreover, in support of the outcomes of the present study, several other scholars reported that co-application of nitrogen significantly boosted the level of antioxidant enzymes in soybean [56], Catharanthus roseus [57], and blueberry [58]. Nitrogen serves as a first line of defense against internal and environmental oxidative stressors [17,21,59,60].…”
Section: Discussionsupporting
confidence: 89%
“…The elimination of H 2 O 2 might be due to the immediate strengthening of SOD, CAT, and POD activities (Figure 8), and the increased content of free amino acids (Figure 5E,F) by higher nitrogen application. Moreover, in support of the outcomes of the present study, several other scholars reported that co-application of nitrogen significantly boosted the level of antioxidant enzymes in soybean [56], Catharanthus roseus [57], and blueberry [58]. Nitrogen serves as a first line of defense against internal and environmental oxidative stressors [17,21,59,60].…”
Section: Discussionsupporting
confidence: 89%
“…Despite that in previous results we observed a differential response on physiological and antioxidant parameters to N fertilization during 4 days (Yañez-Mansilla et al, 2014), there are not studies about N concentration in leaves that maintain a high antioxidant performance in blueberries at the long-term. We hypothesized that there is N concentration threshold that ensure a high phenolic concentration and antioxidant capacity without detrimental effects on plant performance.…”
Section: Introductioncontrasting
confidence: 95%
“…Later on, plants were grown under the following N treatments: 0, 9, 18, 28 or 38 mM N. The N treatments were applied based on differential NH 4 NO 3 levels in the culture media, and they were chosen in order to exceed the N sufficiency level associated with adequate photosynthetic performance and plant growth at the short-term (Yañez-Mansilla et al, 2014). Nutrient solutions were replaced every 7 days and aerated during the course of experiment with an aquarium pump.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…Many studies have reported that the leaf lipid peroxidation was increased under both N deficiency and N excess stress conditions. In fact, it was demonstrated that N deficiency increased MDA concentration in Vaccinium corymbosum (Yañez-Mansilla et al, 2014;Yañez-Mansilla et al, 2015). Similar increase of MDA was observed in Myriophyllum spicuatum and Potamogeton crispus leaves under ammonium stress (Jiao et al, 2009;Yin et al, 2016).…”
Section: Discussionmentioning
confidence: 73%
“…However, it is now well known that ammonium is toxic to many plant species, leading to a reduction in growth and alteration in content of amino acids, mineral cations and organic anions (Li et al, 2011). Only few studies about antioxidant responses in crop-plants grown under differential N supply have been conducted (Nimptsch and Pflugmacher, 2007;Yañez-Mansilla et al, 2014;Yañez-Mansilla et al, 2015). Asada and Takahashi (1987) reported that N excess is generally related to the accumulation of ammonium in plant tissues, whereas N deficiency may increase the production of ROS.…”
Section: Introductionmentioning
confidence: 99%